No justification for recognition of the blindsnake genera Anilios and Sundatyphlops (Squamata: Typhlopidae) - Kraus, Fred; Maddock, Simon T. (Zootaxa, 2026)
The clade of blindsnakes historically placed into Ramphotyphlops Fitzinger was divided into several genera in 2014 based on the topology of a molecular phylogeny. We examine the molecular and morphological evidence used for recognizing two of those genera (the diverse Australian Anilios Fitzinger, and the monotypic Lesser Sundan Sundatyphlops Hedges, Marion, Lipp, Marin & Vidal) and find the evidence insufficient to support their distinction. Post hoc attempts at that time to define Anilios and Sundatyphlops using morphological data relied on using among-species averages of within-species means, an arbitrary approach largely driven by pooling species on geographic grounds, which ignored tremendous ranges of overlap in all morphological features claimed to be diagnostic. Three New Guinean species were also arbitrarily assigned to Anilios in the absence of any molecular or morphological evidence. The sole subsequent molecular study that has included the type species of Ramphotyphlops showed it to be sister to but virtually indistinguishable from Anilios. Lastly, all later molecular studies involving these snakes have consistently found the few species of Ramphotyphlops sensu stricto sampled (n = 1–3) to be paraphyletic when Anilios and Sundatyphlops are recognized. Consequently, we find there is no evidentiary basis for recognizing Anilios or Sundatyphlops as valid lineages distinct from Ramphotyphlops, and continuing to do so renders the latter paraphyletic; thus, we synonymize Anilios and Sundatyphlops with Ramphotyphlops. The taxonomic muddling created by recognizing these genera has persisted because consistently poor sampling of non-Australian members of Ramphotyphlops has not allowed for well-supported clarification of relationships among those lineages